Impact of exercise-induced DNA damage repair on age-related muscle weakness and sarcopenia - Zhu, Lingyan; Su, Yiping; Su, Zhanguo (Frontiers in Genetics, 2026)
Sarcopenia, the progressive and generalized loss of skeletal muscle mass, strength, and function with aging, poses a significant public health challenge. A key contributor to sarcopenia is the accumulation of DNA damage, both nuclear and mitochondrial, coupled with a decline in DNA repair efficiency. This genomic instability, exacerbated by chronic oxidative stress and inflammation, impairs critical cellular processes including protein synthesis, mitochondrial function, and satellite cell regenerative capacity, ultimately leading to myofiber atrophy and weakness. Intriguingly, regular physical exercise, while acutely inducing transient DNA damage, concurrently activates and enhances DNA damage repair pathways, serving as a powerful physiological modulator of genomic integrity. This review comprehensively explores the intricate interplay between exercise, DNA damage, and DNA repair in the context of age-related muscle decline. We delve into the molecular hallmarks of DNA damage (e.g., 8-OHdG, SSBs, DSBs) and the major repair mechanisms (BER, NER, MMR, HR, NHEJ), detailing how acute exercise modalities (e.g., high-intensity interval training, resistance training) induce specific damage types primarily via reactive oxygen species. Crucially, we synthesize emerging evidence suggesting that chronic exercise training may upregulate the efficiency and capacity of DNA repair enzymes, particularly OGG1 in base excision repair, thereby mitigating the accumulation of deleterious genomic lesions. This exercise-induced enhancement of DNA repair directly contributes to maintaining mitochondrial health, preserving muscle stem cell function, and combating cellular senescence and inflammation, ultimately delaying or ameliorating sarcopenia and improving muscle functional outcomes in older adults. We highlight critical gaps in understanding the precise modulation of all repair pathways by exercise and propose future research directions, including advanced biomarker development and personalized exercise prescriptions, to harness the therapeutic potential of DNA repair for healthy muscle aging.